2020
DOI: 10.47067/ramss.v3i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Performance Appraisal on Employees’ Satisfaction: A Case Study of University of Peshawar, Khyber Pakhtunkhwa, Pakistan

Abstract: The purpose of this study is to identify the effect of performance appraisal on employees’ satisfaction in university of Peshawar, Khyber Pakhtunkhwa (KP), Pakistan. We collected data from 60 administrative employees of university of Peshawar using survey questionnaire. We distributed 100 questionnaires among the employees of university of Peshawar, out of which 60 were returned back, so the response rate was 60 %. Findings of this study revealed that performance appraisal significantly and positively affect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…After all, motivation sustains employee performance toward organizational goals and objectives, particularly in a post-pandemic environment in which organizational culture is declining. Work motivation has been linked to employees' satisfaction with their compensation (e.g., Ghanzanfar et al, 2011;Khan & Mufti, 2012;Tanjung et al, 2022).…”
Section: Motivation Theorymentioning
confidence: 99%
“…After all, motivation sustains employee performance toward organizational goals and objectives, particularly in a post-pandemic environment in which organizational culture is declining. Work motivation has been linked to employees' satisfaction with their compensation (e.g., Ghanzanfar et al, 2011;Khan & Mufti, 2012;Tanjung et al, 2022).…”
Section: Motivation Theorymentioning
confidence: 99%
“…Furthermore, (Khan et al, 2020) highlighted the impact of performance appraisal on employees' satisfaction, indicating that a significant percentage of employees perceived the performance appraisal system as ineffective. The impact of performance appraisal extends beyond individual employee attitudes to organizational outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When there are accurate performance indicators, the PAP provides information that enables grounded decision making and that prevents the abuse of power by the appraiser (He et al, 2020). In light of the above, Khan et al (2020a) suggested that satisfaction with the PA involves two elements: the PAP and the results of the PA per se.…”
Section: The Perception Of the Usefulness And Accuracy Of The Perform...mentioning
confidence: 99%